Efficiency of Selected Drone Flight Algorithms in Increasing the Level of Ad-Hoc Network Connectivity Without Knowing the Location of Disconnected Nodes - Jaroslaw MICHALAK (Communications of International Proceedings, 2021)
The article presents an assessment of the possibility of using drones to increase the connectivity of an ad-hoc wireless network. Effectiveness of four drone flight route determining algorithms – working with different policies and different sets of network information – were compared. The common assumption is the lack of information about the location of disconnected nodes, which must be searched for blindly. Computer simulations were used to compare the efficiency of each algorithm. The degree of network connectivity was assessed in relation to flight distance (flight time), network density and the drone's radio range. Under the assumed conditions, the so-called Mesh Route algorithm of the drone's route (see definition in chapter 4), which assumes checking the entire expected network operation area turned out to be the only solution that guarantees obtaining a full network connectivity.
Keywords: Clustered Network; Connectivity; Wireless System; Drone; UAV; Matlab